Linking Participatory Poverty Assessments to Policy and Policymaking : Experience from Vietnam - Turk, Carrie (World Bank, Washington, DC, 2014)
The year 1999 was important for poverty-related research, and policy development in Vietnam. The General Statistics Office had collected household data in the second Vietnam Living Standards Survey in 1998, and made it available for analysis in 1999. And four participatory poverty assessments (PPAs) were implemented during 1999. The author's case study describes how government agencies, donors, and nongovernmental organizations collaborated in implementing the PPAs. The considerable amount of qualitative information about poverty produced in Vietnam over the past eight to ten years has rarely grabbed the attention of policymakers, who tend to view such information as "unscientific" and lacking in credibility. By contrast, the PPAs implemented in 1999 have been widely circulated, used, and quoted. What was different about those PPAs that led their findings to be brought into local, and national policy debates, as previous findings had not been? Working partnerships among donors, and nongovernmental organizations were important, and helped build consensus on the research findings, but more crucial was the active engagement of government partners from the very early stages. Establishing a Poverty Working Group provided a structure for implementing the PPAs, for feeding analysis through to the poverty assessment, and for keeping government fully involved. The Poverty Working Group now supports the government in drafting its poverty reduction strategy. Strong World Bank leadership, financial support from the U.K. Department for International Development, the technical expertise, and commitment of the PPA partners agencies, and the availability of recent high-quality household survey data, played an important part in ensuring the PPAs' credibility.